Hepcidin Gene Co-Option Balancing Paternal Immune Protection and Male Pregnancy - Xiao, Wanghong; Chen, Zelin; Zhang, Yanhong; Wu, Yongli; Jiang, Han; Zhang, Huixian; Qu, Meng; Lin, Qiang; Qin, Geng (Frontiers in Immunology, 2022)
Viviparity has originated independently more than 150 times in vertebrates, while the male pregnancy only emerged in Syngnathidae fishes, such as seahorses. The typical male pregnancy seahorses have closed sophisticated brood pouch that act as both uterus and placenta, representing an excellent model system for studying the evolutionary process of paternal immune protection. Phylogenetic analysis indicated that the hampII gene family has multiple tandem duplicated genes and shows independent lineage-specific expansion in seahorses, and they had the highest ratio of nonsynonymous substitutions to synonymous substitutions (dN/dS) in the seahorse phylogenetic branch. The expression levels of hampIIs in the brood pouch placenta were significantly higher during pregnancy than non-pregnancy. Both LPS stimulation test in vivo and cytotoxicity test in vitro proved the immunological protection function of hampIIs against pathogen infection in seahorse. Besides, seahorse hampII peptides exhibit weaker antibacterial function, but stronger agglutination and free endotoxin inhibition. We assumed that the modified immunological function seemed to be a trade-off between the resistance to microbial attack and offspring protection. In brief, this study suggests that the rapid co-option of hampIIs contribute to the evolutionary adaption to paternal immune care during male pregnancy.